THE FIGURATIVE LANGUAGE IN MATA NAJWA TALKSHOW’S NOTES - Ruth Stevy Hutajulu; Muhammad Natsir (State University of Medan, 2012)
Abstract The purpose of this article is to show through concrete examples about how figurative language used in notes. The notes texts were taken from The Year-End Record of Mata Najwa Talk Show. The central is to analyze the types of figurative language that used in Mata Najwa Talkshow’s notes, that contain Simile, Metaphor, Metonymy, Synecdoche, Personification, Hyperbole, Apostrophe, Allegory, Paradox, Understatement and Irony. 15 notes were taken as the data by using documentary technique and were analyzed by using descriptive qualitative technique. It was found that Irony is the dominant type used in the notes. It means that the notes contain of the insinuation to an object or circumstances. Keywords : mata najwa, notes, figurative language, metrotv